The Refugee Crisis - A Shared Human Condition: An Old Testament Perspective - Wright, Christopher JH (Transformation, 2018)
This article provides an introduction to what the Old Testament has to say regarding displacement and displaced people - refugees, migrants and the marginalized members of society. It surveys the instructions regarding the correct attitude and protective actions owed to 'the stranger' found in the Old Testament Law and it points to the divine preference to side with the suffering and the vulnerable evident in the Old Testament Prophets. Although not an exhaustive treatment of Old Testament passages tackling this topic, the discussion helps make clear the fact that God is particularly concerned with justice and care for the disadvantaged members of the society, including aliens, refugees and migrants. The conclusion of the article calls the readers to consider some of the missiological-ethical implications of such concern in our contexts today.